2014
DOI: 10.1074/jbc.m113.535070
|View full text |Cite
|
Sign up to set email alerts
|

Binding of CD157 Protein to Fibronectin Regulates Cell Adhesion and Spreading

Abstract: Background: Surface CD157 modulates leukocyte and ovarian cancer cell adhesion and migration through the interaction with an unknown ligand. Results: CD157 binds heparin-binding domains of numerous extracellular matrix proteins with high affinity. Conclusion:The interaction of CD157 with extracellular matrix proteins is instrumental in the regulation of cell adhesion. Significance: These findings provide valuable insights into the biological mechanism responsible for the nonenzymatic functions of CD157.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…More recent studies have shown that CD157 regulates cell adhesion to the extracellular matrix (ECM) [19] and binds selected ECM proteins, including fibronectin [20] which has a central role in mesenchymal differentiation [21]. This data indicates that CD157 is involved in EMT and suggests that the CD157/ECM interplay in the tumor microenvironment could be critical in determining the aggressiveness of CD157-positive tumors by facilitating the EMT differentiation program ongoing in biphasic MPM [5, 22].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown that CD157 regulates cell adhesion to the extracellular matrix (ECM) [19] and binds selected ECM proteins, including fibronectin [20] which has a central role in mesenchymal differentiation [21]. This data indicates that CD157 is involved in EMT and suggests that the CD157/ECM interplay in the tumor microenvironment could be critical in determining the aggressiveness of CD157-positive tumors by facilitating the EMT differentiation program ongoing in biphasic MPM [5, 22].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that BST-1 promotes pre-B-cell growth and is involved in early T-cell development (30). As reported by Morone et al CD157 plays a crucial role in cell-extracellular matrix interaction (33). As reported by Morone et al CD157 plays a crucial role in cell-extracellular matrix interaction (33).…”
Section: Introductionmentioning
confidence: 92%
“…CD157 is a crucial factor for the mobility of human neutrophils (31,32) and is involved in the transmigration of monocytes (29). As reported by Morone et al CD157 plays a crucial role in cell-extracellular matrix interaction (33). In mesenchymal stem cells BST-1 has pivotal regulatory functions (34).…”
Section: Introductionmentioning
confidence: 93%
“…Despite not containing intracellular domains, CD157 was able to interact with integrins CD18 and CD29 on human neutrophils and monocytes, forming supramolecular complexes that activated signaling pathways to modulate transendothelial migration and adhesion to extracellular matrix components [81,82]. A number of extracellular matrix proteins containing heparin-binding domains were indeed shown to be high affinity non-substrate ligands for CD157, including fibronectin and fibrinogen [81,83].…”
Section: Cd157 a Cd38 Paralogue Is Important For The Host Response mentioning
confidence: 99%